Morphological annexation and its role in the Arabization - Sheta, Jamal Mostafa (Journal of Arabic Language Sciences and Literature, 2022)
This research shows the annexation of the Arabic morphology: definition, and its importance, and the conditions, and forms, also shows his role in the arabization of foreign words, as adopted by the ancient tributary streams of verbal expansion and absorb the word piety. The research came in four sections, the first section dealt with: the definition of placement and its purpose and significance, types and origins. The second topic dealt with weights attached to the names, weights attached to deeds. And the third on: the role of annexation in the localization when eloquent Arabs, and linguists veterans. And the fourth theme dealt: the role of placement in the localization of the modern era. The research has come to the importance of placement as a way of how to cope with the influx of foreign terms, and that the ancients were more use in the localization and integration of Arab words foreign a dictionary. In the modern era, the forms of annexation were virtually non-existent in Arabization and were limited to only a few forms.
Keywords: annexation; Arabization; Morphology; forms